Hydrolysis of flavanones from orange peel and evaluation of anticancer potential using naringinase immobilized on corn cob powder (2025)
The management of waste from global orange production represents an environmental and economic challenge. In this study, the extraction of flavanones from orange peel albedo was optimized as a sustainable and economical alternative to purified substrates. The extracts obtained, rich in naringin, narirutin, hesperidin, neohesperidin and rutin, were enzymatically hydrolyzed by the naringinase complex, whose α-L-rhamnosidase and β-D-glucosidase activities transformed these compounds into prunin and naringenin. Their effect was evaluated in cell viability assays in the SW480 line, identifying compounds with potential biological activity in colon cancer prevention. Purification of naringinase increased its affinity for α-L-rhamnosidase activity, while its immobilization in corn cob powder allowed improving its reusability and stability, retaining up to 75 % of its initial activity after 10 consecutive cycles. By using whole extracts without purification, this study proposes a more viable and scalable approach for the valorization of citrus waste for biological purposes.